2020
DOI: 10.48550/arxiv.2012.01347
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Reducing the Athena WFI charged particle background: Results from Geant4 simulations

Abstract: One of the science goals of the Wide Field Imager (WFI) on ESA's Athena X-ray observatory is to map hot gas structures in the universe, such as clusters and groups of galaxies and the intergalactic medium. These deep observations of faint diffuse sources require low background and the best possible knowledge of that background. The WFI Background Working Group is approaching this problem from a variety of directions. Here we present analysis of Geant4 simulations of cosmic ray particles interacting with the st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 1 publication
0
1
0
Order By: Relevance
“…Recent work (Wilkins et al 2020;Grant et al 2020) using simulations of the upcoming ATHENA mission has shown that machine learning methods may be able to independently estimate the probability that an individual event is associated with the background. The methods presented here can be considered complimentary to those, in the sense that the our framework can be used in situations where such high fidelity simulations of X-ray photon interactions with telescope hardware are not available or feasible.…”
Section: Discussionmentioning
confidence: 99%
“…Recent work (Wilkins et al 2020;Grant et al 2020) using simulations of the upcoming ATHENA mission has shown that machine learning methods may be able to independently estimate the probability that an individual event is associated with the background. The methods presented here can be considered complimentary to those, in the sense that the our framework can be used in situations where such high fidelity simulations of X-ray photon interactions with telescope hardware are not available or feasible.…”
Section: Discussionmentioning
confidence: 99%